PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA GURU SMK NEGERI - Astuti, Indah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractIn a general way, this research is based on the thought that the importance of the teacher’s job satisfaction to increase the quality of the teachers’ performance.This research is aimed at having the information, analyzing and summarizing the influence between the principal’s leadership style and the organizational climate partially and simultaneously towards the teacher’s job satisfaction. This research is descriptive (expose facto) with the quantitative approach. The observation data about the principal’s leadership style (X1), the organizational climate (X2) and the teachers’ job satisfaction (Y) are carried out by spreading the questionnaires to the teachers of the Vocational School, on 1st Sub District, Sambas Regency. The results of this research indicates that in the partial way the principals’ leadership style influences the teacher’s job satisfaction positively with the regressive coefficient for 0,302, in the organizational climate influences the teachers’ job satisfaction positively with the regressive coefficient for 0,232 and in the simultaneous way influences the teachers’ job satisfaction and the organizational climate positively to the teachers of the Vocational School, on 1st Sub District, Sambas Regency with the coefficient determination for 0,266 or 26,6% indicating that the percentage giving of the principal’s leadership style and the organizational climate towards the teacher’s job satisfaction is for 0,266 or 26,6%, while the rest of 0,734 or 73,4% is fluence by another factor out of this research. Based on this research is very essential for the principal to apply the leadership style which is suitable for the teachers’ levels and create the good organization climate in increasing the teacher’s job satisfaction.Keywords:Leadership Style, Organizational Climate, The Teachers’ Job Satisfaction.